2018
DOI: 10.1177/0265407518787357
|View full text |Cite
|
Sign up to set email alerts
|

Birth status and adult attachment

Abstract: Numerous studies have investigated the effects of having an unwanted or unplanned pregnancy on parents. Less is known about the long-term effects of unwanted or unplanned pregnancy on the child and his or her personality. Here we examined in one correlational study and three experiments the associations between birth status (being unwanted, unplanned, or neither) and adult attachment. In general, being unwanted, and to a lesser extent unplanned, was associated with attachment insecurity. Priming thoughts about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Moreover, for both theoretical and applied reasons, attachment researchers want to know whether specific kinds of experiences are capable of changing the deep-seated ways in which people relate to significant others in their lives (e.g., Arriaga, Kumashiro, Finkel, VanderDrift, & Luchies, 2014; Arriaga, Kumashiro, Simpson, & Overall, 2018; Davila & Kashy, 2009). Identifying such experiences may shed light on potential risk factors for insecurity (e.g., Gillath, Casebier, Canterberry, & Karantzas, 2019) or provide insights into interventions that can promote or enhance security (e.g., Carnelley, Bejinaru, Otway, Baldwin, & Rowe, 2018; Gillath & Karantzas, 2019; McGuire, Gillath, Jackson, & Ingram, 2018; Rowe, Shepstone, Carnelley, Cavanagh, & Millings, 2016). At the core of such investigations is the assumption that the factors identified are associated with changes that do not fade away after a brief period of time.…”
mentioning
confidence: 99%
“…Moreover, for both theoretical and applied reasons, attachment researchers want to know whether specific kinds of experiences are capable of changing the deep-seated ways in which people relate to significant others in their lives (e.g., Arriaga, Kumashiro, Finkel, VanderDrift, & Luchies, 2014; Arriaga, Kumashiro, Simpson, & Overall, 2018; Davila & Kashy, 2009). Identifying such experiences may shed light on potential risk factors for insecurity (e.g., Gillath, Casebier, Canterberry, & Karantzas, 2019) or provide insights into interventions that can promote or enhance security (e.g., Carnelley, Bejinaru, Otway, Baldwin, & Rowe, 2018; Gillath & Karantzas, 2019; McGuire, Gillath, Jackson, & Ingram, 2018; Rowe, Shepstone, Carnelley, Cavanagh, & Millings, 2016). At the core of such investigations is the assumption that the factors identified are associated with changes that do not fade away after a brief period of time.…”
mentioning
confidence: 99%
“…Parent's response to children's needs or in other words, the parent-child relationship is based on the parent attachment style and leads to the attachment style in children. Children's attachment style is an irreplaceable opportunity for emotional and social growth of children; so that, negative early experiences lead to psychological problems and aggression in children and adults [11][12][13][14]. Attachment style continues on the basis of emotions, expectations, active inner patterns, and beliefs in individuals until adulthood, affecting normal and abnormal personal and interpersonal relationships in adulthood [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is the basis of how individuals deal with life issues and the ways of their attitude, actions, and reactions to issues and problems [17]. The mother's attachment style affects her behavior with her child, child's development and growth, personality development, and subsequent attachment relationships [14,18]. Adult attachment research has confirmed that the attachment system is activated under stressful conditions; and individuals with different attachment styles seek to regulate emotions, feelings, and cope with abnormal situations by the ways that reflect their beliefs about themselves and others [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, attachment avoidance is characterized by deactivation of the attachment system. Avoidantly attached individuals tend to deny attachment needs, suppress emotions and to devaluate close relationships (Gillath et al, 2019; Mikulincer & Shaver, 2019; Nolte et al, 2011). Although anxious and avoidant patterns might be functional in terms of survival during infancy and childhood, the affect regulation strategies come along with them have negative impact on the individual’s cognitive, emotional and social development as well as their mental health in adulthood (Adshead, 2018).…”
mentioning
confidence: 99%